Enhancing employee awareness to mitigate the economic and operational impacts of unlawful interference in Abu Dhabi - Mohamad Sharif, Sabri; Saleh Alnuaimi, Amer Ali Saeed; Wekke, Ismail Suardi (Human Resource Management Academic Research Society, 2024)
Awareness of unlawful interference is pivotal for enabling employees to effectively manage and mitigate its impacts on critical areas such as flight delays and cancellations, maintenance and repairs, tourism, stocks, and investments. A thorough review of past studies, this paper aims to identify the significance of unlawful interference and employee’s readiness in Abu Dhabi Airport. The findings of this review reveal that employee awareness is fundamental in reducing flight delays and cancellations, which often result in substantial costs associated with overtime, rescheduling, and operational disruptions. Similarly, employees equipped with knowledge of maintenance and repair protocols can detect potential threats early, avoid unnecessary repairs, and ensure efficient resource utilization at AUH. In the tourism sector, employee readiness to handle security incidents fosters a perception of safety among travelers, encouraging confidence in airport operations. As a vital gateway to the region, AUH plays an essential role in supporting tourism-related industries, such as hospitality and retail. Airports demonstrating robust security through trained employees are better positioned to sustain tourist inflows and support economic growth. Moreover, awareness among employees plays a vital role in stabilizing stocks and investments, as effective management of security threats reassures investors, thereby maintaining confidence in the aviation and tourism sectors. This is particularly important for AUH, which continues to attract global investments as part of its strategic positioning as a leading aviation hub. Future research should delve deeper into how employee awareness of passenger-targeted attacks, airport infrastructure attacks, and false information can enhance their preparedness to control and mitigate the effects of these threats. For instance, investigations could focus on how awareness influences their ability to address the economic impacts of delays, support the tourism industry, and maintain airport infrastructure and maintenance at AUH.